A study of new anhydrous, conducting membranes based on composites of aprotic ionic liquid and cross-linked SPEEK for fuel cell application. (10th January 2015) - Malik, Rajender Singh; Verma, Pawan; Choudhary, Veena
Graphical abstract: Highlights: New composite membranes based on SPEEK/EG/IL were fabricated. Composite membranes exhibit good thermal stability than neat SPEEK and XSPEEK membrane. Proton conductivity of all composite membranes increased with temperature and amount of ionic liquid. Proton conductivity was measured under anhydrous condition in the temperature ranging from 30–140 °C. Abstract: The present study describe the preparation and characterisation of anhydrous proton conducting composite membranes based on sulfonated poly(ether ether ketone) [SPEEK–degree of sulfonation 70–72%]/ethylene glycol [EG]/ionic liquid by solution casting method using water: ethanol (50:50) as solvent. For this purpose several composite membranes were prepared by mixing solution of SPEEK/ethylene glycol (67:33 wt %) in water:ethanol with varying amounts of 1-butyl-3-methyl-imidazolium trifluromethanesulfonate [bmim][OTf] ionic liquid. The cross-linking of SPEEK was carried out by thermal treatment i.e. by heating in vacuum oven at 80 °C (2 h), 100 °C (2 h), 120 °C (2 h) and 135 °C for 16 h. Ethylene glycol was used as a cross-linker for SPEEK to reduce the leaching out of ionic liquid and enhance the mechanical strength of SPEEK membranes. The membranes were characterized for thermal [thermogravimetry analysis], structural [FTIR–ATR], proton conductivity, morphology (XRD, SEM) and leaching out of ionic liquid with water. FTIR studies clearly showed the interactions between SPEEK, EG and ionic liquid. The proton conductivity and dynamic mechanical properties of the composite membranes were investigated at elevated temperature and under anhydrous conditions. Proton conductivity of all the membranes measured in the temperature range of 30–140 °C under anhydrous conditions was in the range of 10 −3 Scm −1 which showed an increase with increase in temperature and amount of ionic liquid.